2022
DOI: 10.3390/polym14071406
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Vulcanization of Polymyrcene and Polyfarnesene Bio-Based Rubbers: Influence of the Chemical Structure over the Vulcanization Process and Mechanical Properties

Abstract: The overuse of fossil-based resources to produce thermoplastic materials and rubbers is dramatically affecting the environment, reflected in its clearest way as global warming. As a way of reducing this, multiple efforts are being undertaken including the use of more sustainable alternatives, for instance, those of natural origin as the main feedstock alternative, therefore having a lower carbon footprint. Contributing to this goal, the synthesis of bio-based rubbers based on β-myrcene and trans-β-farnesene wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…NMR is a powerful tool for studying polymerization reactions. However, cross-linked polymers require a solid NMR technique due to their insolubility . To overcome the limitations that impose the insolubility of PEDOT or PPy polymers or EDOT-Py copolymers, we performed an in situ liquid NMR to monitor the progress of the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…NMR is a powerful tool for studying polymerization reactions. However, cross-linked polymers require a solid NMR technique due to their insolubility . To overcome the limitations that impose the insolubility of PEDOT or PPy polymers or EDOT-Py copolymers, we performed an in situ liquid NMR to monitor the progress of the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to Far polymerization described above, [31,33,34] our research group [53] recently reported that the phosphine-functionalized fluorenyl ligated yttrium (39) catalytic system showed ultra-high activity (completely convert 500 equiv. of Far within 0.5 min) and perfectly 3,4-isoselectivity (3,4-= 100%, mmmm > 99%) for Far polymerization at room temperature (Figure 18).…”
Section: β-Farnsecene (Far)mentioning
confidence: 99%
“…Very recently, they [34] vulcanized PMyr and PFar manufactured by above catalytic system, and the different processes and mechanical properties of corresponding polymers were discussed. After sulfur vulcanization, due to crosslinking with branches, the tensile strengths of PMyr and PFar were decreased compared with those of polybutadiene and polyisoprene.…”
Section: Bio‐based Linear Terpenes As Conjugated Dienes For Rare‐eart...mentioning
confidence: 99%
See 1 more Smart Citation
“…10 Due to its similarity to petroleum-based monomers and its widespread availability in nature, interest in synthesizing homo-and copolymers with different synthetic approaches, starting from β-myrcene, is increasing. Synthetic polymerization methods used for this purpose include ionic polymerization, [11][12][13][14][15] coordination polymerization, 16 controlled radical polymerization [17][18][19] and free radical polymerization. 20,21 The polymer microstructure and final properties of polymyrcenes are strongly dependent on the regioselectivity of the addition step and polymerization conditions (i.e., solvent, temperature, initiator).…”
Section: Introductionmentioning
confidence: 99%